Analysis Of Methods And Systems For Detecting And Countering Uavs. Issue 1 (March 2021) - Basan, Elena; Pshikhopov, Vyacheslav; Lapina, Maria; Mecella, Massimo
Abstract: This article discusses methods for detecting UAVs in the radio frequency range. The analysis of the existing UAV detection systems is carried out. An overview of ways to counter UAVs is presented, in particular, by carrying out attacks on navigation and communication systems. A prototype of the UAV detection system, which is based on the UAV, is presented. The UAV detection function has been implemented based on the analysis of the radio frequency spectrum.